The New Criminal Procedure Code. Reality or fiction - Burgos Mariño, Víctor (2020)
All changes implies challenges, and them will be only surpassed if in the context of this changes the actors in that play fulfill the expectation, otherwise, we wont reach the goals, and the blame will not be attributed to one person, all of us will be blame for it. The current Penal Procedural Reformation, implemented as a result of the application of the New Procedural Criminal Code in the Judicial District of La Libertad, is not the exception for what was previously showed; this implementation is not that simple, since beyond the change of a normative body which is important is the change of a deep inquisitive culture rooted in the mind of all the actors of criminaljustice, as well as the contribution of those who indirectly take part in it. Being this thus, the success of the beginning of the reform extends the mere normative aspect and demands from all its actors an active participation in order to reach the proposed goals, therefore, that it is not only some people´s responsibility, it is all of us